2014
DOI: 10.1021/nl502598s
|View full text |Cite
|
Sign up to set email alerts
|

Giant Magnetoconductance Oscillations in Hybrid Superconductor−Semiconductor Core/Shell Nanowire Devices

Abstract: The magnetotransport of GaAs/InAs core/shell nanowires contacted by two superconducting Nb electrodes is investigated, where the InAs shell forms a tube-like conductive channel around the highly resistive GaAs core. By applying a magnetic field along the nanowire axis, regular magnetoconductance oscillations with an amplitude in the order of e(2)/h are observed. The oscillation amplitude is found to be larger by 2 orders of magnitude compared to the measurements of a reference sample with normal metal contacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 34 publications
3
25
0
Order By: Relevance
“…In particular, an axial field may lead to Aharonov-Bohm (AB) field-periodic modulation of the electron energy spectrum [11] and, if the phase-coherent length exceeds the perimeter of the NW, the observation of magnetoconductance oscillations [12,13]. Indeed, several observations of AB-like oscillations in magnetotransport experiments performed on radial heterostructures have been reported [14][15][16][17][18]. Recently, Gül et al [16] observed fluxperiodic magnetoconductance oscillations in GaAs/InAs coreshell NWs.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, an axial field may lead to Aharonov-Bohm (AB) field-periodic modulation of the electron energy spectrum [11] and, if the phase-coherent length exceeds the perimeter of the NW, the observation of magnetoconductance oscillations [12,13]. Indeed, several observations of AB-like oscillations in magnetotransport experiments performed on radial heterostructures have been reported [14][15][16][17][18]. Recently, Gül et al [16] observed fluxperiodic magnetoconductance oscillations in GaAs/InAs coreshell NWs.…”
Section: Introductionmentioning
confidence: 99%
“…In Fig. 6b, the differential resistance dV/dI as a function of the bias voltage is plotted at temperatures from 2 to 8 K. The distinct peaks at 2 and 3 K, are recognized as the result from Andreev reflection under a superconducting state [43,44], in which electrons/holes will be reflected from the interfaces of junction. The Andreev reflection and resultant excess conductance originates from the interfaces in Sn/CNT/Sn junctions of Sn@CNT NRs.…”
Section: Superconductivity Of Sn@cnt Nrs Below T Cmentioning
confidence: 99%
“…In contrast, in 3.11(b) several states with doubly-connected topology are occupied, the electron density is more delocalized and the AB-like magnetoconductance oscillations persist. The latter is indeed the usual regime in magnetotransport experiments, [96,97] what explains why only oscillating profiles have been reported in literature. …”
Section: Low-magnetic-field Regimementioning
confidence: 80%
“…However, typical profiles show flux periodic oscillations, [96,97] and a situation with constant G has never been observed experimentally. This may be due to the fact that the most common device configuration for manipulating the electron density is to use a back-gate, instead of a gate-all-around.…”
Section: Low-magnetic-field Regimementioning
confidence: 95%
See 1 more Smart Citation